Biphasic Hyalinizing Psammomatous Renal Cell Carcinoma (BHP RCC): A Distinctive Neoplasm Associated With Somatic NF2 Mutations. (July 2020) - Argani, Pedram; Reuter, Victor E.; Eble, John N.; Vlatkovic, Ljiljana; Yaskiv, Oksana; Swanson, David; Dickson, Brendan C.; Antonescu, Cristina R.; Matoso, Andres; Gagan, Jeffrey; Palsgrove, Doreen N.
Abstract : We report 8 cases of a distinctive, previously undescribed renal cell carcinoma associated with somatic mutations in the neurofibromin 2 ( NF2 ) gene. All patients were adults, ranging from 51 to 78 years of age and of cases of known sex 6 of 7 were males. The carcinomas were predominantly unencapsulated, and all had a rounded, nodular interface with the native kidney. The neoplasms were all solid with papillary architecture evident in most cases (7/8), while 1 was only tubular. All cases were biphasic, characterized by larger and smaller carcinoma cells. The smaller cells clustered around basement membrane material similar to the characteristic pattern of the t(6;11) renal cell carcinoma associated with TFEB gene fusions. In 6 of 8 carcinomas, branching nodules of small cells clustered around basement membrane material within larger acini yielding a distinctive glomeruloid pattern. In 6 of 8 carcinomas, the small cells were focally spindle-shaped and unassociated with the basement membrane material. The stroma was sclerotic in all 8 carcinomas, and all 8 contained psammoma bodies that were abundant in 2. In some carcinomas, focal or predominant areas had a less distinctive appearance; 2 had areas that resembled clear cell renal cell carcinoma, 2 had high-grade eosinophilic areas, while 1 had branching tubular architecture that resembled mucinous tubular and spindle cell carcinoma. Two carcinomas demonstrated cellular necrosis. Although we have minimal clinical follow-up, 1 case presented with distant metastasis, progressed and resulted in patient death. While NF2 mutations may be found in other established renal cell carcinoma subtypes (often as secondary genetic alterations), they are potentially the genetic driver of this distinctive entity. Abstract : Supplemental Digital Content is available in the text.